2020
DOI: 10.3389/fpls.2019.01793
|View full text |Cite
|
Sign up to set email alerts
|

Fractionating of Calcium in Tuber and Leaf Tissues Explains the Calcium Deficiency Symptoms in Potato Plant Overexpressing CAX1

Abstract: Consistent with reports on other plants we recently reported that a potato transgenic line (AT010901) overexpressing sCAX1 show classic symptoms of calcium deficiency shoot tip injury, leaf curling, leaf margin necrosis and tuber internal defects such as hollow heart and brown spots. The present study was undertaken to quantify calcium in various fraction of leaf and tuber tissues of this transgenic and wild type potato clones to understand the development of these deficiency symptoms at normal calcium nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…In these two reports, no deleterious alternations in plant growth and morphological traits between transgenic plants and wild types were observed. In contrast, Zorrilla et al [48] and Gao et al [49] reported that sCAX-expressing potatoes showed shoot rip necrosis and hollow heart, while the total and tuber Ca 2+ concentrations were higher than those of the wild-type. The authors demonstrated that this result was due to sCAX-expressing potatoes sequestering Ca 2+ in vacuoles as calcium oxalate crystals, reducing the water-soluble Ca 2+ concentration.…”
Section: Effects Of Genes Encoding Ca 2+ Antiportersmentioning
confidence: 91%
See 3 more Smart Citations
“…In these two reports, no deleterious alternations in plant growth and morphological traits between transgenic plants and wild types were observed. In contrast, Zorrilla et al [48] and Gao et al [49] reported that sCAX-expressing potatoes showed shoot rip necrosis and hollow heart, while the total and tuber Ca 2+ concentrations were higher than those of the wild-type. The authors demonstrated that this result was due to sCAX-expressing potatoes sequestering Ca 2+ in vacuoles as calcium oxalate crystals, reducing the water-soluble Ca 2+ concentration.…”
Section: Effects Of Genes Encoding Ca 2+ Antiportersmentioning
confidence: 91%
“…To determine the role of gene expression in the occurrence of Ca deficiency disorders and/or Ca accumulation, 37 articles were reviewed in detail (Tables 1 and 2 and Figures 1 and 2). Twenty-six of the thirty-seven reports showed an association between Ca deficiency and/or Ca accumulation and the expression of Ca 2+ -movement-related genes (Ca 2+ antiporters [27,29,32,35,36,39,[42][43][44][45][46][47][48][49][50]53], calreticulin [30,[51][52][53], Ca 2+ -ATPase [35,36,39,54,55], Ca 2+ channels [55][56][57][58], and PME [35,59]). Of the remaining studies, five studies identified QTLs that described variation in tipburn incidence [25,26,33,34,38].…”
Section: Synthesizing Current Knowledge Regarding the Role Of Gene Expression In The Occurrence Of Ca 2+ Deficiency Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…That is because linking nutrient deficiency symptoms with physiological functions offers the simplest yet wide-reaching means capable of explaining and predicting the Ca 2+ status in crop plants with high genetic diversity 1 . Because of this reason, the Ca 2+ deficiency symptoms, relatively appearing first and very early 9 , 21 , 22 , have been investigated 4 , 9 , 19 , 20 , 23 and used as diagnostic criteria for plants and soils 1 , 24 . This knowledge is acutely needed, especially now to sustain plant productivity against climate-change-induced challenging conditions such as mineral stress, water scarceness, increased groundwater salinity, soil pests build-up, etc.…”
Section: Introductionmentioning
confidence: 99%